Hidden Cities Urban Space, Geolocated Apps and Public History in Early Modern Europe - Nevola, Fabrizio; Rosenthal, David; Terpstra, Nicholas (Taylor & Francis, 2022)
This groundbreaking collection explores the convergence of the spatial and digital turns through a suite of smartphone apps (Hidden Cities) that present research-led itineraries in early modern cities as public history. The Hidden Cities apps have expanded from an initial case example of Renaissance Florence to a further five historic European cities. This collection considers how the medium structures new methodologies for site-based historical research, while also providing a platform for public history experiences that go beyond typical heritage priorities. It also presents guidelines for user experience design that reconciles the interests of researchers and end users. A central section of the volume presents the underpinning original scholarship that shapes the locative app trails, illustrating how historical research can be translated into public-facing work. The final section examines how history, delivered in the format of geolocated apps, offers new opportunities for collaboration and innovation: from the creation of museums without walls, connecting objects in collections to their original settings, to informing decision-making in city tourism management. Hidden Cities is a valuable resource for upper-level undergraduates, postgraduates, and scholars across a variety of disciplines including urban history, public history, museum studies, art and architecture, and digital humanities.